Study on adsorption characteristics of biochars and their modified biochars for removal of organic dyes from aqueous solution - Zhang Xiaojuan; Cheng Wenwen; Wang Jialu; Lei Yanhui; Yang Xueqin; Duan Quan; Duan Wenfeng; Zhang Yutao (Green Processing and Synthesis)
To address organic dye pollution and agricultural waste comprehensive utilization, the biochar (ZB) was prepared using Rosa roxburghii residue as the material for preparation. Three modified biochars (ZBO, ZBS, and ZBH) were created using NaOH, Na2S, and H3PO4 as modifying agents. The morphology, structure, pore size, and elemental composition of biochars were characterized and analyzed by a combination of FTIR, SEM-EDS, and N2 adsorption–desorption techniques. Furthermore, the adsorption performance of the as-prepared biochars was investigated in the adsorption of RhB and MB dye process. The experimental findings showed that adsorption equilibrium for these dyes was achieved in 180 min. Moreover, the dye adsorption on biochars followed a pseudo-second-order kinetic equation. For the biochar (ZB), the Langmuir equation proved to be more appropriate than the Freundlich equation. In contrast, the Freundlich equation was more apt for the modified biochars. More importantly, Pearson's correlation analysis revealed that the adsorption rate and capacity of RhB positively correlated with the specific pore volume, t-plot micropore area, and BET surface area, but a negative one with the pore size. The MB adsorption showed the opposite correlations. This study reveals a novel biochar for adsorbing organic dyes, which provides a strategy for the treatment of Rosa roxburghii residue.